2009
DOI: 10.1037/a0017259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on discounting of delayed rewards in attention deficit/hyperactivity disorder.

Abstract: Impulsivity is a central component of attention-deficit/hyperactivity disorder (ADHD). Delay discounting, or a preference for smaller, immediate rewards over larger, delayed rewards is considered an important aspect of impulsivity, and delay-related impulsivity has been emphasized in etiological models of ADHD. The current study examined whether stimulant medication, an effective treatment for ADHD, reduces discounting of delayed experiential and hypothetical rewards among 49 children (age 9-12 years) with ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 59 publications
13
99
0
5
Order By: Relevance
“…A growing literature suggests that dopaminergic abnormalities underlie impairments in decision making, which accompany a number of neuropsychiatric disorders (Rahman et al, 2001), but the effects of dopaminergic drugs on risk-taking behavior are inconsistent. For example, administration of dopamine agonists promotes risky choices in Parkinson's disease (Cools and D'Esposito, 2011) and in healthy controls (Riba et al, 2008), but reduces risk-taking behaviors (DeVito et al, 2008) and impulsive decisions (Shiels et al, 2009) in children with attention deficit hyperactivity disorder. Although the effects of amphetamine and haloperidol are not limited to dopaminergic systems, the administration of either drug, despite the opposite effects on dopamine signaling increases motivation to gamble in problem gamblers Poulos, 2004, 2007), suggesting that the link between dopamine signaling and risk-taking behavior is not simply a linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…A growing literature suggests that dopaminergic abnormalities underlie impairments in decision making, which accompany a number of neuropsychiatric disorders (Rahman et al, 2001), but the effects of dopaminergic drugs on risk-taking behavior are inconsistent. For example, administration of dopamine agonists promotes risky choices in Parkinson's disease (Cools and D'Esposito, 2011) and in healthy controls (Riba et al, 2008), but reduces risk-taking behaviors (DeVito et al, 2008) and impulsive decisions (Shiels et al, 2009) in children with attention deficit hyperactivity disorder. Although the effects of amphetamine and haloperidol are not limited to dopaminergic systems, the administration of either drug, despite the opposite effects on dopamine signaling increases motivation to gamble in problem gamblers Poulos, 2004, 2007), suggesting that the link between dopamine signaling and risk-taking behavior is not simply a linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has also shown that administration of amphetamine and the D 2 receptor antagonist, haloperidol, can prime cognitions that promote gambling behavior as well as enhance its reinforcement value in samples of individuals with gambling problems (Zack and Poulos, 2004). Finally, the mixed dopamine and noradrenaline agent, methylphenidate, has also been shown to ameliorate the risk-taking behavior of children with diagnosis of DSM-IV attention-deficit-hyperactivity disorder (ADHD) when asked to place 'bets' on their previous decisions being correct (DeVito et al, 2008), as well as reducing the number of impulsive decisions in the performance of delay-discounting tasks (Shiels et al, 2009). Dopaminergic agents also appear to improve decision making in adult clinical populations.…”
Section: Dopamine and Decision Makingmentioning
confidence: 99%
“…Understanding individual differences in how people trade off reward magnitude and delay (i.e., delay discounting) is of high ecological and clinical relevance. Rates of delay discounting predict important outcomes in education, health, and savings and are abnormal in a range of psychiatric conditions, including addiction and attention-deficit hyperactivity disorder (Madden et al, 1997;Vuchinich and Simpson, 1998;Kirby and Petry, 1999;Mitchell, 1999;Marco et al, 2009;Shiels et al, 2009).…”
Section: Introductionmentioning
confidence: 99%